Phase relations of calcic amphibole- orthoamphibole-chlorite-talc assemblages, with applications to ultramafic rocks from the KTB pilot hole, Bavaria - Schmädicke, Esther; et al. (International Journal of Earth Sciences, 1997)
Lenses of ultramafic rocks intercalated within a metagabbro-amphibolite sequence were encountered in the KTB pilot hole. A pervasive metamorphic overprint formed the dominating assemblage calcic amphibole-orthoamphibole- chlorite-talc. In this study the phase relations of ultramafic rocks are investigated in order to (a) constrain the stability field of this assemblage in general, and (b) define the equilibrium pressure-temperature (P-T) conditions of this assemblage in the ultramafic rocks from the KTB borehole. For that purpose, phase equilibria were calculated in the model systems CaO-MgO-Al 2O3-SiO2-H2O (CMASH) and CaO-MgO-FeO-Al2O3-SiO2-H2O (CMFASH). Thereby, the continuous compositional change of solid solutions with pressure and temperature was modeled, including the Tschermak's substitution and the MgFe-1 exchange. Based on these results, petrogenetic grids were constructed, revealing that calcic amphibole-orthoamphibole-chlorite-talc assemblages cover a stability field of < 650-770°C/1 → 14 kbar (CMASH) and < 550-650°C/1 → 14 kbar (CMFASH), respectively. This explains the widespread occurrence of the considered assemblage. Based on the bulk rock composition of the KTB samples, a special P-T diagram was constructed, limiting the stability field of the calcic amphibole-orthoamphibole-chlorite- talc assemblage. At 580°C the stability field extends from 6 to 14 kbar pressure, and shrinks to 10-11 kbar at 630°C. Conventional estimates using the mineral compositions of the KTB samples yield a temperature around 630°C, at which the calculated stability field of calcic amphibole-orthoamphibole-chlorite-talc extends from 10 to 11 kbar. © Springer-Verlag 1997.
UnivIS-Import:2017-03-24:Pub.1997.nat.dgeo.IGM.profes_1.phaser
Keywords: Bohemian massif; Geothermobarometry; KTB; Metamorphic rocks; Phase petrology; Ultramafic rocks; Variscides; Zone of Erbendorf-Vohenstrauss